Understanding of anti-cancer properties of Neolamarckia cadamba leaves on breast cancer: prospective therapeutic Neolamarckia cadamba extract - Khatib, Alfi; Hashim, Ridzwan; Mohammad, Mardhiah; Draman, Samsul; Abdul Jamil, Muhammad Mahadi; Johan, Muhammad Farid; Hassan, Habibah (2018)
Introduction:Breast cancer becomes the global health problem throughout the world. It is rated as the second most common cancer occurrence after lung cancer and the leading cause of death among women. The rising of breast cancer cases years by years is really worrying. Due to the side effects of current treatments and resistance towards chemotropic drugs, it is important to evaluate new chemopreventive agents from various sources particularly plants. Method: Neolamarckia cadamba leaves were rinsed, dried and pulverised into coarse powder. The powdered leaves were sonicated in ethanol. The filtered extract were concentrated and freeze dried. In in vitro analysis, Neolamarckia cadamba leaves extracts (NCE) were tested on breast cancer cell line (MCF-7). Different concentration of sample extracts were administered on MCF-7 cells to find the 50% inhibitory concentration [IC50] after 72 hours of treatment. The treated MCF-7 cells were observed under microscope to observe the morphological changes. Cytotoxicity assay was conducted on normal cells to test the extract toxicity using IC50 value. Flowcytometric analysis were conducted to evaluate apoptosis induction and cell cycle arrest using the IC50 value of extracts against MCF-7 cancer cells.Quantitative PCR (qPCR) were conducted to investigate the gene expression with regards to induction of apoptosis and cell cycle arrest in treated MCF-7 cells. Phytochemical screening were conducted by TPC and TFC assay as well as GCMS analysis.Result: MCF-7 treated cells showed decreased in cell growth with increased concentration of NCE. The value of IC50 obtain was at 0.2 mg/ml. Under microscopic observation, the MCF-7 treated cells showed the features of apoptosis including cell shrinkage, cell blebbing and apoptotic cells No significant toxic effect were observed on both normal fibroblast cell line after treated with NCE. Moreover, flowcytometric analysis on apoptosis induction demonstrated that NCE induced apoptosis and cell cycle arrest at G0/G1 phase. qPCR assay of gene expression showed up-regulated of apoptosis related genes (cytochrome C, Baxcaspase 9 and caspase 7) and down-regulated of Bcl-2and caspase 8were suggested that NCE induced apoptosis via intrinsic mitochondrial pathway. Meanwhile, the up-regulated of p21 and down-regulated of CDK2 indicated that the NCE cause cell cycle arrest. Phenol and flavonoid compound were detected in the NCE. Several compoundswere presented in the NCE includephenol,2,4-bis(1,1-dimethyllethyl)-, levoglucosan, d-Glucose, beta-D-(+)-Talopyranose, hexadecanoic acid, myo-Inositol, oleic acid and octadecanoic acid.Conclusion: Neolamarckia cadamba leaves have a potential to act as chemopreventive agent for breast cancer treatment.